Studies on Potassium Fixation and its Relationship with Chemical Characteristics of Some Desertic Soils of Western Rajasthan - Aggarwal, R K; Sharma, V K; Dhir, R P (Annals of Arid Zone, 2016)
Potassium fixation in some soil groups of Jodhpur and Nagaur districts of arid Rajasthan has been studied. The K-fixation capacities of grey brown loam, light brown loam, Luni alluvium and hard pan soils, on an average were: 0.535, 0.451, 0.180 and 0.140 meq/1OOg soil respectively. Sub-surface soils showed higher K-fixation capacities. K-fixation capacity was found to bear a significant positive relationship with organic matter content, fixed K and non-exchangeable K. Highly significant correlation was found between K-fixation capacity and CEC and clay content of soil. Organic matter in soil was found to have depressing effect on K-fixation capacity when regressed along with CEC of soil. In these soils, either CEC or clay content can be an important indicator in determining the extent of K-fixation capacity.